Structure and evolution of Apetala3, a sex-linked gene in Silene latifolia - Cegan, Radim; Marais, Gabriel Ab; Kubekova, Hana; Blavet, Nicolas; Widmer, Alex; Vyskot, Boris; Dolezel, Jaroslav; Safár, Jan; Hobza, Roman (BMC plant biology, 2010)
BACKGROUND: The evolution of sex chromosomes is often accompanied by gene or chromosome rearrangements. Recently, the gene AP3 was characterized in the dioecious plant species Silene latifolia. It was suggested that this gene had been transferred from an autosome to the Y chromosome. RESULTS: In the present study we provide evidence for the existence of an X linked copy of the AP3 gene. We further show that the Y copy is probably located in a chromosomal region where recombination restriction occurred during the first steps of sex chromosome evolution. A comparison of X and Y copies did not reveal any clear signs of degenerative processes in exon regions. Instead, both X and Y copies show evidence for relaxed selection compared to the autosomal orthologues in S. vulgaris and S. conica. We further found that promoter sequences differ significantly. Comparison of the genic region of AP3 between the X and Y alleles and the corresponding autosomal copies in the gynodioecious species S. vulgaris revealed a massive accumulation of retrotransposons within one intron of the Y copy of AP3. Analysis of the genomic distribution of these repetitive elements does not indicate that these elements played an important role in the size increase characteristic of the Y chromosome. However, in silico expression analysis shows biased expression of individual domains of the identified retroelements in male plants. CONCLUSIONS: We characterized the structure and evolution of AP3, a sex linked gene with copies on the X and Y chromosomes in the dioecious plant S. latifolia. These copies showed complementary expression patterns and relaxed evolution at protein level compared to autosomal orthologues, which suggests subfunctionalization. One intron of the Y-linked allele was invaded by retrotransposons that display sex-specific expression patterns that are similar to the expression pattern of the corresponding allele, which suggests that these transposable elements may have influenced evolution of expression patterns of the Y copy. These data could help researchers decipher the role of transposable elements in degenerative processes during sex chromosome evolution.
Keywords: exony; Genes, Plant; Silene; Exons; Sequence Analysis, DNA; Repetitive Sequences, Nucleic Acid; sekvenční analýza DNA; molekulární evoluce; promotorové oblasti (genetika); Evolution, Molecular; retroelementy; Plant Proteins; chromozomy rostlin; Chromosomes, Plant; regulace genové exprese u rostlin; Retroelements; Introns; DNA rostlinná; DNA, Plant; introny; Gene Expression Regulation, Plant; Promoter Regions, Genetic; repetitivní sekvence nukleových kyselin; rostlinné geny; Alleles; alely; rostlinné proteiny